2019
DOI: 10.3389/fnins.2019.00601
|View full text |Cite
|
Sign up to set email alerts
|

The Peripheral Nervous System in Amyotrophic Lateral Sclerosis: Opportunities for Translational Research

Abstract: Although amyotrophic lateral sclerosis (ALS) has been considered as a disorder of the motor neuron (MN) cell body, recent evidences show the non-cell-autonomous pathogenic nature of the disease. Axonal degeneration, loss of peripheral axons and destruction of nerve terminals are early events in the disease pathogenic cascade, anticipating MN degeneration, and the onset of clinical symptoms. Therefore, although ALS and peripheral axonal neuropathies should be differentiated in clinical practice, they also share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 274 publications
(267 reference statements)
1
33
0
Order By: Relevance
“…An interesting finding is that 28% of the variants were identified in CMT2/dSMA genes. These data confirm the emerging genetic pleiotropy of ALS [1,2,9,58]. More specifically, in relation to the specific design of our panel, our data suggest an overlap with other diseases sharing degeneration of motor axons and neurons as a common feature, such as the axonal hereditary neuropathies [9].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…An interesting finding is that 28% of the variants were identified in CMT2/dSMA genes. These data confirm the emerging genetic pleiotropy of ALS [1,2,9,58]. More specifically, in relation to the specific design of our panel, our data suggest an overlap with other diseases sharing degeneration of motor axons and neurons as a common feature, such as the axonal hereditary neuropathies [9].…”
Section: Discussionsupporting
confidence: 84%
“…However, genetic heterogeneity, pleiotropy, and nonpenetrance are incompletely understood issues in ALS [1,2,4,6]. Furthermore, some aspects of the ALS phenotype, are shared with other neurodegenerative, neuropsychiatric, and neuromuscular diseases, such as axonal hereditary Charcot-Marie-Tooth neuropathy (CMT2), distal hereditary motor neuropathy (dHMN), or hereditary spastic paraplegia (HSP), which could implicate similar genes in their pathology [1,2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between mitochondrial fission and fusion leads to abnormal mitochondrial morphology, underlies axonal damage, and is a potential therapeutic target for treating SPG15 and SPG48 (Denton et al, 2018). The ER and mitochondria form complex sites of interactions known as mitochondria-associated membranes (Gentile et al, 2019). Decreased ER-mitochondria association can occur as a result of loss-of-function mutations in SIGMAR1, leading to impaired retrograde transport and, ultimately, to axonal degeneration and MN death (Bernard-Marissal et al, 2015;Watanabe et al, 2016).…”
Section: Axonal Energy Supplymentioning
confidence: 99%
“…This disorder manifests in the form of progressive painless weakness of several muscle groups including those involved in respiratory movements, which invariably leads to respiratory failure and death (1). In addition, an increasing number of studies have recently reported sensory and autonomic symptoms in ALS patients, supporting an involvement of the peripheral nervous system in the pathogenic mechanisms of this disease (2).…”
Section: Introductionmentioning
confidence: 85%